2010
DOI: 10.1371/journal.pcbi.1000738
|View full text |Cite
|
Sign up to set email alerts
|

On the Conservation of the Slow Conformational Dynamics within the Amino Acid Kinase Family: NAGK the Paradigm

Abstract: N-Acetyl-L-Glutamate Kinase (NAGK) is the structural paradigm for examining the catalytic mechanisms and dynamics of amino acid kinase family members. Given that the slow conformational dynamics of the NAGK (at the microseconds time scale or slower) may be rate-limiting, it is of importance to assess the mechanisms of the most cooperative modes of motion intrinsically accessible to this enzyme. Here, we present the results from normal mode analysis using an elastic network model representation, which shows tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 63 publications
(95 reference statements)
3
30
0
Order By: Relevance
“…Note that our previous work [34] showed that ANM modes 1–3 were instrumental in accommodating the structural changes at the ATP-binding site, but had practically no effect on the NAG-binding site. This nicely illustrates how the enzyme takes advantage of different types of motions accessible to its native structure for achieving different types of functional motions.…”
Section: Resultsmentioning
confidence: 88%
“…Note that our previous work [34] showed that ANM modes 1–3 were instrumental in accommodating the structural changes at the ATP-binding site, but had practically no effect on the NAG-binding site. This nicely illustrates how the enzyme takes advantage of different types of motions accessible to its native structure for achieving different types of functional motions.…”
Section: Resultsmentioning
confidence: 88%
“…These studies typically use coarse-grained models, such as normal mode analysis, to infer catalytic time scale motional similarities between protein folds (58). Generally, these studies also involve the direct comparison of simulated data with crystallographically resolved and/or NMR-resolved enzymes in apo and ligand-bound forms, inferring dynamic information through, but not limited to, residual dipolar coupling measurements and/or Debye-Waller factors (B-factors) (59). The latter provides a rough approximation of residue flexibility in protein crystals, albeit with no clear definition of dynamic time scale.…”
Section: Discussionmentioning
confidence: 99%
“…This behavior is characteristic of molecular systems that sample inactive conformations with a high probability, such that small perturbations are sufficient to drive the molecule or complex into the inactive state (44)(45)(46)(47). Likewise, the sensitivity of cpSRP43 to point mutations suggests that its SBD is at the threshold of a cooperative conformational change required to attain a chaperone-active conformation.…”
Section: Discussionmentioning
confidence: 99%